DIGITAL CONTROL IN HERITAGE TRUST MANAGEMENT - Akramov Akmaljon (Scholar Express Journals, 2024)
This article emphasizes the main concepts related to the implementation of digital control in trust management, the powers of state authorities in the implementation of digital control. Also, specific issues related to ensuring the security of a person's assets after his death and maintaining his digital security are emphasized
Keywords: digital property; digital heritage; authority; digital assets